Increasing Efficiency in Furniture Remanufacturing with Ahp and the Seci Model - Sepulveda-Rojas, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This article proposes the application of the AHP method in an office furniture remanufacturing company, with the aim of optimizing knowledge retention and management. In particular, it seeks to establish the optimal retrieval route for returned products. To this end, a bibliographic analysis was first carried out, which revealed the scarcity of previous studies on the subject, thus validating the relevance of this work. Subsequently, a practical application of the AHP method was carried out to define the weighting matrix of the evaluation criteria, applied to three specific pieces of furniture, which confirmed the effectiveness of the tool. In a complementary manner, Nonaka and Takeuchi’s SECI model of knowledge management was used, guaranteeing the continuous updating of the matrices and the adequate retention of knowledge in the company. This methodology will increase the volume of remanufactured products and improve operating margins. By reaping both the economic and environmental benefits of this practice, the company will be able to reduce costs, generate additional revenue, improve its corporate image, and build customer loyalty. At the same time, this study promotes the sustainability and sustainable development of this practice within the company and, by extension, in the broader office furniture manufacturing industry. It can serve as a reference for other companies in this sector across different countries. © 2024 by the authors.